Return predictability and complicated countries : 125.899 research report : a research report presented in partial fulfillment of the requirements for the degree of Master of Finance, Massey University, Albany, Auckland, New Zealand - Nguyen, The Hung (Massey University, 2014)
Prices should instantly reflect information according to the efficient markets hypothesis (EMH). Hong and Stein (1999), however, suggest that the information processing environment will affect price discovery because of the gradual diffusion of information. This paper investigates the roles of information processing complexity in the price discovery process across countries. We hypothesise that the same piece of relevant macroeconomic information can be incorporated into stock prices at different speeds, depending on the complication of information environment in each country. The results show that returns for less complicated countries can predict future returns for more complicated countries with the out-of-sample R2's ranging from 3% to 14%. We find that the predictability induced by the complications in information processing is consistent at both group level and country level. Moreover, our results prevail after we control for regional effects.
Keywords: Stock prices; Stock market; Rate of return